1997
DOI: 10.1063/1.365198
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic characterization of laser-induced plasma created during welding with a pulsed Nd:YAG laser

Abstract: A spectroscopic study of a laser-induced plume created during the welding of stainless steel and other materials (iron and chromium) has been carried out. A pulsed Nd:YAG laser of 1000 W average power is used. The evolutions of the electron temperature and electron density have been studied for several welding parameters. We use working powers from 300 to 900 W and pulse durations between 1.5 and 5 ms. The influence of shielding gases like nitrogen and argon has been taken into account. Temperature and density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(67 citation statements)
references
References 11 publications
3
64
0
Order By: Relevance
“…Three different shielding gases, namely Ar, He and N 2 , were used to provide face shielding. The shielding gas nozzle had a diameter of 4 mm and was arranged at an angle of 25 to the workpiece. The shielding gas was delivered with flow rates of 10 L min À1 , 16 L min…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different shielding gases, namely Ar, He and N 2 , were used to provide face shielding. The shielding gas nozzle had a diameter of 4 mm and was arranged at an angle of 25 to the workpiece. The shielding gas was delivered with flow rates of 10 L min À1 , 16 L min…”
Section: Methodsmentioning
confidence: 99%
“…[22][23][24] However, in Nd:YAG laser welding, laser absorption in the plume is very weak, 25) and therefore the plume volume has a lesser influence on the penetration depth. Consequently, the penetration depths identified in the present study are very similar despite the fact that the plumes formed under the three shielding gases are quite different in size (as shown Fig.…”
Section: Depth Of Penetration and D=w Ratiomentioning
confidence: 99%
“…The T e reflects the heat input, while the N e is closely associated with the evaporation and the ionization of the materials. The T e can be deduced by relative intensities of two spectral lines of the same element under same ionization stage if the plasma is in local thermal equilibrium (LTE) [19][20][21][22]. The assumption of LTE is fulfilled when the N e is high enough so that 18 …”
Section: Electron Temperature and Electron Density Of The Plasmamentioning
confidence: 99%
“…Moreover, the optical properties of the laser-induced plasma during welding may distort the three dimensional data set due to refractive index change and consequently may lead to reduced keyhole depth. However, spectroscopic characterization of laser-induced plasma created during welding of stainless steel with a pulsed Nd:YAG laser by Lacroix et al [9] revealed a refractive index of n = (1 -2.1 × 10 −5 ) at the same wavelength as the light source wavelength of the Lessmüller OCT system. Clearly, the influence of the plasma's refractive index on the OCT measurements is negligible.…”
Section: In-process Quality Control With Octmentioning
confidence: 99%